PERSEPSI DAN PARTISIPASI PETANI DALAM PENERAPAN USAHATANI KONSERVASI (Studi Kasus Petani Sayuran Di Hulu DAS Jeneberang) - Nuraeni, Nuraeni; Sugiyanto, Sugiyanto; Kusuma, Zaenal; Syafrial, Syafrial (Bumi Lestari; Vol 12 No 1 (2012), 2012)
Utilization of dry land resources most available in the upper watershed which hilly landform and heavy rainfall. This leads to erosion event and resulting decrease of land productivity. Thus, it needs application of conservation techniques to optimize the utilization of dry land in the upstream watershed. The aims of study are to identify the conservation application on the farm vegetables, to examine the perception of farmers towards conservation farming, and to assess the participation of farmers in conservation farming in the Upper Jeneberang watershed. Research sites in the upstream watershed Jeneberang, Gowa in South Sulawesi. The population is vegetable farming. The respondents did sampling randomly with number 182 farming. Data analysis methods used is descriptive analysis that is equipped with a qualitative analysis that are category and comparison analysis. The results showed the level of farmers' perceptions about the benefits of conservation has been generally high, the benefits to the prevention of erosion (61.54%), soil fertility (58.89%), availability of water (64.84%) and prevention of floods and landslides (67.58 %). The high perception of farmers on the benefits of conservation is not followed by the participation of farmers in conservation farming. This is evident from the participation in counseling following the generally very low (56.59%), participation in the application of generally low conservation (27.47%), while participation in the maintenance has been generally high (31.32%).
Keywords: conservation farming, vegetable farm, conservation, perception, participation